High-frequency oscillatory ventilation versus conventional ventilation in pediatric patients with acute lung injury: outcomes evaluation - Ahmed R. Rezk; Mai A. Mohamed; Mohamed H. Elkenawy; Nehad Bakry; Ahmed Omran (Egyptian Pediatric Association Gazette, 2022)
Abstract Background With the development of medical technology and advancements of intensive care units, many types of mechanical ventilators are recruited in the management of acute respiratory distress syndrome (ARDS)/acute lung injury (ALI). We evaluated the outcome of the high-frequency oscillatory ventilation (HFOV) compared to conventional mechanical ventilation (CMV) in pediatric patients with critical respiratory situations mainly ALI or ARDS. A prospective cohort study was performed from 2019 to 2020 in the pediatric intensive care unit (PICU). The following data were recorded: demographic and clinical data, length of PICU stay, mechanical ventilation days, and mortality percentages. Results Fifty cases who fulfilled the inclusion criteria were divided into two groups, 24 patients on HFOV from the start and the other 26 were admitted on rescue HFOV after the failure of CMV. There was no statistically significant difference between the two groups regarding the age (p = 0.571) and the oxygenation index (OI) (p = 0.651). Early HFOV demonstrated shorter length of PICU stay and fewer days on mechanical ventilation. The mortality rate was less with the application of early HFOV compared to rescue HFOV. Conclusions Early admission on HFOV can be a safe option in the management of patients with critical lung situation as ARDS/ALI.